Overview of the Standards and Objectives of Implementing the Dengue Hemorrhagic Fever (DHF) Control Policy through the One House One Mosquito Net Movement Program at the Rahandouna Village Health Center, Kendari City - Muhammad Arsyi, La Ode; Azizi Jayadipraja, Erwin; Abdurrahman, Syawal (Waluya The International Science of Health Journal, 2025)
Introduction:Dengue fever remains a serious health problem in Indonesia, including in Kendari City, with cases occurring annually. In 2023, Kendari City successfully reduced dengue fever morbidity through the "1 house, 1 mosquito larvae" initiative. This study aims to describe the "1 house, 1 mosquito larvae" initiative at the Poasia Community Health Center.Method:Qualitative research and case study design were conducted in 2024. The key informants in this study were the coordinators of infectious disease control at community health centers, while general informants included the heads of community health centers, movement managers, village heads, and the heads of the infectious disease prevention and control section of the Kendari City Health Office.Result:Demonstrate conformity with the policy implementation theory and guidelines of this movement which include standards and objectives, characteristics of implementing organizations, communication between implementing organizations, disposition, and environment (social, economic, and political).Conclusion:There is a need for training in the use of Android-based applications for coordinators and supervisors, forming a team with the Village Office and socializing how to become a Coordinator and Supervisor to the Community.